Development of animal structure practicum e-module on canva - Ramadansur, Rahmat; Dinata, Marta; Sembiring, Al Khudri; Ichwany, R. Tasya Nur; Robi, Putri Fajar; Rizky, Ramanda (JURNAL BIOEDUKATIKA, 2024)
This research explores innovation in learning through the integration of information technology, particularly e-modules for teaching animal structure laboratories using Canva. Using an R&D approach with the 4-D development model, the study involved 3 validators and 17 students at Lancang Kuning University. Data were analyzed descriptively qualitatively and quantitatively, indicating high levels of validity for subject matter, language, and media experts. Student responses to the e-module were also very positive. The research findings indicate that the Animal Structure Laboratory E-Module created with Canva is highly valid and suitable for use in learning, reinforcing the use of technology in an educational context.